Surveys in social research. 5th ed. - de Vaus, David (London, 2002)
"This work provides advice on how to plan, conduct and analyze social surveys. It emphasizes the links between theory and research, the logic and interpretation of statistics, and the practices of social research. The fifth edition includes a new chapter on ethics and a glossary. It assumes no background in statistical analysis, and gives readers the tools they need to come to grips with this often confusing field."